Empowerment of former migrant workers: Triple bottom line framework - Sri Wahjuni Latifah; Agung Riyardi Riyardi (Journal of Innovation in Business and Economics, 2020)
This study aims to analyze the empowerment of former Indonesian migrant workers, especially in the potential of running small businesses. The research data were collected by interview and literature study and the data were classified and analyzed using SWOT analysis. The SWOT analysis results are interpreted with a triple bottom line framework approach, which includes financing, environment, and social. The results of the study show that the migrant workers in Donomulyo district have sufficiently good capital in terms of financing, environment, especially in natural resources, and the social environment that allows business growth. One of the main challenges is human resources, ranging from entrepreneurial spirit to minimal managerial skills. Therefore, stakeholders must focus on programs that prioritize improving entrepreneurial skills and managerial aspects.